Psychometric Properties of a Simplified Chinese Version of the Secondary Trauma Questionnaire in a Potentially Traumatized Study Sample - Yan, Ya-jun; Jiang, Lichen; Hu, Mu-li; Wang, Ling; Xu, Xin; Jin, Zhi-shuai; Song, Yu; Lu, Zhang-xiu; Chen, You-qiao; Li, Na-ni; Su, Jun; Wu, Da-xing; et al. (Frontiers in Psychology, 2020)
Background Screening for secondary traumatic stress (STS) is lacking in China. It is unclear whether Western models of STS can be adapted satisfactorily for use in non-Western regions. The 20-item Secondary Trauma Questionnaire (STQ) is a self-report measure of traumatic stress symptoms in individuals who have been influenced indirectly by suicide or violent injury of people important to the respondents. Methods Here, we assessed the psychometric properties of a newly developed Chinese version of the STQ in a potentially traumatized sample (N = 875) composed of doctors, nurses, teachers, civic administration staff, and social workers in China. We performed reliability and validity analyses. Subsequently, we split the total sample into two subsamples for exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) for measurement invariance analyses. Results The full scale demonstrated good internal consistency (Cronbach’s α = 0.95–0.97), convergent validity, discriminant validity, and factorial validity. CFA affirmed a one-factor structure; the configural, metric, scalar, and strict invariances of the STQ were acceptable across genders. Conclusion The present results indicate that the STQ is a reliable and valid self-report assessment for use with potentially traumatized people in China, and further supports the notion that the STQ is amenable to additional future cross-cultural adaptation.